Linking Air Pollution Data and Adverse Birth Outcomes: Environmental Public Health Tracking in New York State. (March 2015) - Brown, Jessica M.; Harris, Gerald; Pantea, Cristian; Hwang, Syni-An; Talbot, Thomas O.
Abstract : Background: Studies investigating associations between ambient air pollution and fetal growth and gestational duration have reported inconclusive findings. Objectives: The study goal was to use the Environmental Public Health Tracking Network to describe the association between exposure to particulate matter (PM2.5 ) and ozone and term low birth weight (TLBW) in New York State. Methods: Birth data for the years 2001-2006 were linked to Census data and hierarchical Bayesian modeled air pollution data. Daily 8-hour maximums for ozone and daily average PM2.5 estimates were averaged by trimester and exposure quartiles. The Environmental Public Health Tracking Academic Center for Excellence at Rutgers University partnered with New York and several other states to create a statistical program that uses logistic regression to determine the association between air pollution exposure and TLBW. Results: There were no consistent dose-response relationships between the pollutants and TLBW. Ozone exposure was associated with a higher risk of TLBW only in the first trimester, but these results were not statistically significant. Exposure to the third quartile of ozone for the full gestational period had negative associations with TLBW (odds ratio = 0.86; 95% confidence interval, 0.81-0.92). Conclusion: Collaboration within the Environmental Public Health Tracking Network to share methods and data for research proved feasible and efficient in assessing the relationship of air pollutants to adverse birth outcomes. This study finds little evidence to support positive associations between exposure to ozone or PM2.5 and TLBW in New York State. Abstract : Supplemental Digital Content is Available in the Text.This study describes the Environmental Public Health Tracking Network for linking air pollution data and adverse birth outcomes in New York State.